1996
DOI: 10.1111/j.1365-2389.1996.tb01414.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of chemical composition of soil solutions collected by zero‐tension plate lysimeters with those from ceramic‐cup lysimeters in a forest soil

Abstract: We analysed the chemistry of solutions collected from soil by zero-tension plate lysimeters and cup lysimeters connected to a constant suction (600 hPa) under Douglas fir in the Beaujolais mountains (France). The chemistry of zero-tension lysimeters' (ZTL) and tension lysimeters' (TL) solutions differed enormously: TL solutions were most concentrated in Si, NHi-N, NO;-N, Cl-, Mg2+ and A13+ and TOC, whereas Ca2+ and K+ concentrations were greater in ZTL solutions. Organic matter (OM) greatly influenced the solu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
1
5

Year Published

1998
1998
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(45 citation statements)
references
References 15 publications
(14 reference statements)
2
37
1
5
Order By: Relevance
“…In natural forest ecosystems with high precipitation, the dominant pathway for nutrient loss is via surface runoff and subsurface drainage (Nelson, 1970;Waring and Schlesinger, 1985;Hornung, 1990;Reynolds et al, 1990;Cavelier et al, 1997). Thus, estimation of the output of nutrients through these hydrological fluxes is one conventional part of the nutrient budget studies in forest ecosystems (Jordan, 1982;Marques et al, 1996;McDowell, 1998;Hafkenscheid, 2000).…”
Section: Introductionmentioning
confidence: 94%
“…In natural forest ecosystems with high precipitation, the dominant pathway for nutrient loss is via surface runoff and subsurface drainage (Nelson, 1970;Waring and Schlesinger, 1985;Hornung, 1990;Reynolds et al, 1990;Cavelier et al, 1997). Thus, estimation of the output of nutrients through these hydrological fluxes is one conventional part of the nutrient budget studies in forest ecosystems (Jordan, 1982;Marques et al, 1996;McDowell, 1998;Hafkenscheid, 2000).…”
Section: Introductionmentioning
confidence: 94%
“…It should be stressed that our soiltype was ideal for their use. In more Ðssured soils there is greater uncertainty, mainly because of doubt over whether the cups sample soil matrix or Ðssure water (Grossman and Udluft 1991 ;Marques et al 1996). The spatial variability of nitrate can also restrict the accuracy of leaching measurements, but we tried to minimise this e †ect by deriving treatment means from 18 individual sampling points.…”
Section: Comparison Of Methods For Measuring Nitrate-n Concentrationsmentioning
confidence: 99%
“…3b). Marques et al (1996) reported major differences in the qualities of waters collected by zero tension plate and ceramic cup tension lysimeters. They suggested that solutes in waters collected by the zero tension plate lysimeter are affected mainly by organic matter mineralization in the forest floor and the A1 horizon, and these undergo little interaction in vertical transfer in the soil.…”
Section: Alum Dose and Doc Removalmentioning
confidence: 99%